(untitled) (Global Journal of Science Frontier Research, 2022)
Taking into account the peculiarities of interaction, the equations of motion are proposed, from which correspondences with the main parameters of both kinematics and dynamics are found. It is shown that it is the potential of interaction with the third-party partners that is the parameter, the presence, change, and redistribution of which the content of all three Newton’s laws is interpreted.